Nutritional Status of Children under Age 5 Years in India: A Cross-sectional Study - Mr. Santosh D. Saruk; Dr. Rajesh Dase; Dr. Pandurang Thatkar; Mr. Shriram N. Kargaonkar (The Bioscan, 2024)
Malnutrition has been associated to a variety of health problems, including increased rates of morbidity and mortality, a delay in cognitive development, and a loss in adult productivity. All of these problems impact people of all ages, including children and adults. According to the National Family Health Survey-5 (NFHS-5), the rate of malnutrition in India is the highest of any country in the world. According to the findings of the survey, there are around 35.5% of youngsters in India who are underweight. As a direct consequence of this, India currently holds the title of having the highest rate of malnutrition in all of the other countries of the globe. As part of this cross-sectional study, the nutritional well-being of India's younger children (those who are under the age of five) will be investigated. A multi-stage random selection approach was used to pick one thousand homes in India, each of which contained at least one kid younger than five years old. These residences were gathered from different parts of the country. It is required that there be at least one child living in each of these homes. In order to evaluate the nutritional status of the children, their anthropometric measurements were measured. The subject's weight, height, and upper arm circumference at the midpoint were some of the measurements that were taken. By conducting interviews with the children's parents and any other caregivers, we were able to collect data about the children's eating patterns in addition to demographic information about the children. The findings can be put to use in the development of initiatives that will effectively improve the nutritional condition of Indian children and minimize the harmful consequences that malnutrition has on that nation. The social desirability bias and informational memory bias that were present in the parents and caregivers who participated in the study might have had an effect on the findings of the study. Given that the research was of a cross-sectional nature, it was also possible that it would have been difficult to demonstrate a causal link between the variables. This was yet another disadvantage of the study.